Adjustable Maintenance Dosing with Budesonide/Formoterol Reduces Asthma Exacerbations Compared with Traditional Fixed Dosing: A Five-Month Multicentre Canadian Study - J Mark FitzGerlad; Malcolm R Sears; Louis-Philippe Boulet; Allan B Becker; Andrew R McIvor; Pierre Ernst; Natasha M Smiljanic-Georgijev; Joanna SM Lee (Canadian Respiratory Journal)
BACKGROUND: Adjustable maintenance dosing with budesonide/formoterol in a single inhaler (Symbicort, AstraZeneca, Lund, Sweden) may provide a convenient means of maintaining asthma control with the minimum effective medication level.